Consumption and Material Culture in Sixteenth-Century Ireland - FLAVIN, SUSAN (University of Bristol, 2011)
This thesis argues that Irish consumption underwent major changes over the course of the sixteenth century, based primarily on evidence from eleven annual Bristol `particular? accounts and Port Books. The study uses the customs data as a statistical framework on which to establish how, why and to what extent patterns of consumption changed in Ireland. The available qualitative evidence, including wills, archaeological evidence, pictorial evidence, contemporary literature and legislation are considered alongside the quantitative data to examine who was consuming the increasing range and volume of commodities that were imported into Ireland from Bristol and what changing consumption patterns reveal about the nature of Ireland?s economy, society and culture during this period. The thesis also shows how the Exchequer customs accounts can be used to shed light on the changing consumption patterns / material culture of a pre-consumer society, with the intent of revealing the potential value of this source for consumption historians. This work contributes to the current historiography in a number of important ways. It shifts the chronological focus of consumption studies from the conventional eighteenth and nineteenth centuries to the sixteenth century, thus illustrating that marked changes in consumption can occur even in the most unlikely of pre-industrial societies. Also, by focusing on Ireland during this critical period, the lead up to the Elizabethan re-conquest, the thesis shows the extent to which changes in consumption habits map onto major political and social changes, thereby shedding light on the impact of colonisation and conquest on the acquisition, and interpretation of everyday goods. The study also makes a distinctive methodological contribution to consumption historiography, which currently suffers from a distinct lack of quantitative based studies.
PUBLISHED
Keywords: Anglo-Irish Trade; Consumption